A comprehensive analysis of lightweight 8-bit sboxes from iterative structures. (November 2022) - Chen, Jinhai; Gong, Zheng; Tang, Yufeng; Dong, Xinfeng
Abstract: Massive data needs to be cryptographically handled in emerging IoT applications. Therefore the design and analysis of lightweight symmetric-key primitives become a research hotspot. Theoretically, symmetric-key cryptograms should be secure against differential, linear and other proposed structural cryptanalysis. In addition to these cryptographic properties, software and hardware costs are also pivotal for resource constrained devices. Traditionally, 4-bit sboxes are widely used in lightweight cryptography due to their efficiency. In this paper, we investigate the iterative constructions of lightweight 8-bit sboxes. Our proposals contain 8-bit sboxes constructed with the Feistel, Lai–Massey and SPN structures, which are iterated with the published lightweight 4-bit sboxes or non-bijective functions. Moreover, we propose 8-bit sboxes under the generalized Feistel network (GFN), which are suitable for software and hardware implementations. Based on the bitslicing method, software and hardware performances are analyzed with their CPU cycles and Gate Equivalent (GE). Compare to the published lightweight 8-bit sboxes with iterative structures, our proposals achieve similar software performance, whilst enjoying better algebraic degrees and less GE costs in hardware implementation. Highlights: The lightweight 8-bit sboxes with iterative structures are profoundly investigated. Lightweight 4-bit sboxes are used to construct 8-bit sboxes through iterative Feistel, Lai–Massey, and SPN structures. New lightweight 8-bit sbox constructions are proposed with GFN, combining with some specified search strategies. The cryptographic properties are analyzed along with the performance. The results show that our proposed 8-bit sboxes provide new insights for lightweight block ciphers.